ہجرت ِمدینہ بطورِ ذریعۂ قیامِ امن : ایک تجزیاتی مطالعہMigration to Madina as a Source of Establishment of Peace: An Analytical Study (Al-Qamar, 2021)
Migration is the ancient sunnah of all the prophets (A.S) .Hazrat Muhammad ﷺ also migrated to Madina  because  of  the atrocities committed by Makkans,  their less  inclination  to Islam  and  the command  (order) of  Allah .Migration  is done to achieve  great objects and it results in lot of benefits .One  of them is establishment of peace. The people who migrate , get rid of cruelties  of natives .In this sense,  it is  a source  of peace  for immigrants  as it  happened  with   the  immigrants  of migration   of (Abyssinia) and Madina .Islamic state  was established  after  ‘Madina Migration’ .In this way,  the natives  and others  nations  enjoyed  the establishment  of peace .There  are many  aspects  of this establishment  of peace as uniformity of human race, elimination of riots, unification and cooperation, justice system, educational referms , security of  fundamental rights , legal retribution and implementation of Hdood, Blood money and  beginning of accountability .The international relations and issues after migration  all these phenomenon become the source of establishment of peace . Blessings of Medina  migration  were not  only  source  of peace  for the people  of this era  but  also for the whole humanity.
Keywords: Medina; Migration; source; peace